Project Based Game Learning Effectiveness In 21st Century Classrooms: A Literature Review - Angel Ardila Suci Q A; Ketut Agustini; I Kadek Suartama (South Sulawesi Education Development (SSED), 2025)
21st century education demands a learning model that can foster critical thinking, creativity, collaboration and communication skills. One of the emerging models to answer this challenge is Project-Based Game Learning (PjGBL), which integrates a project-based approach with elements of educational games. This study aims to examine the application of PjGBL through the Systematic Literature Review (SLR) method on 13 selected articles in the range of 2020-2024. Articles were analyzed based on research subjects, education levels, subjects, learner characteristics, focus of learning outcomes, and approaches used. The review results show that PjGBL is most commonly applied at the higher education level (S1), especially in Mathematics and Science subjects, and is dominantly applied to students with visual kinesthetic characteristics. The focus of the most frequently developed outcomes are critical thinking (7 articles), collaboration and creativity (5 articles). In terms of approach, constructivism is the most dominant approach because it is aligned with the principles of active and participatory learning. This model is also most effective in middle grades with between 30 and 60 students. This study illustrates that PjGBL is a potential innovative learning model in supporting the development of 21st century competencies holistically.